Sustainable Value as a Tool for Corporate Performance Management within New Public Management Framework - Fuka Jan; Lešáková Petra (My University, 2016)
This paper deals with implementation of Sustainable Value approach into Corporate Performance Management within New Public Management framework and its use in public administration environment. Nowadays, public organizations are looking for ways to become more efficient and, in some respect, to gain a competitive advantage but also put the emphasis on sustainable development. The concept of use selected management methods of private sector and their use in public administration is called New Public Management. It has not clearly defined boundaries and it is still open to new possibilities and tools. Due to increasing pressure on organizations, no matter if private or public, on compliance with the principles of sustainable development, authors define crucial economic, environmental and social indicators which should be included in overall performance evaluation of public administration environment. In general implementing sustainable development principles into organizational performance management should bring wide range of effects, for example contribution to cost savings, better efficiency of processes, or strengthen relationship within the community and customer loyalty. In practical terms, the aim of this paper is to introduce Sustainable Value as a proper tool for Corporate Performance Management, which seems to be suitable, within New Public Management framework, for use by regional governments to measure and evaluate performance.
Udržitelná hodnota jako nástroj pro Corporate Performance Management v rámci New Public Managementu
Keywords: Corporate Performance Management; New Public Management; indicators; public sector; private sector; Sustainable Value; Corporate Performance Management; New Public Management; ukazatele; veřejný sektor; soukromý sektor; udržitelná hodnota